PENERAPAN PEMBELAJARAN ACTIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI MADRASAH - Hasan Baharun (Nurul Jadid University, 2015)
Active learning approach is implemented on a morality of learning Aqidah Akhlaq learning invites students to actively learn. When students learnactively, meaning they dominate the learning activity, so with this activitystudents actively use the brain, either to find the main ideas, solveproblems, or apply what they had learned into a problem that exists in reallife. Through active learning approach this addition, students are invitedto participate in the learning process, not only mentally but also physicallyinvolved. In this way students will typically feel more pleasant atmosphereso that the learning outcomes can be maximized.